An Analysis of Figurative Language on The Lyrics of Coldplay's Selected Song - Ferawaty Puspitorini; Haris Hamdani (ITScience (Information Technology and Science), 2021)
The purpose of this study was to know the kinds of figurative language used in selected lyrics of Coldplay song. This research was designed to identify some figurative language by understanding the general meaning when they are used in the lyrics of songs. The technique of descriptive analysis offered to analyze data by reading the data, then identifying the figurative language used in the lyrics of the song. After identifying some figurative languages then they are categorized into some kinds of figurative languages. Then, the general meaning of figurative language by identifying the lexical meaning and contextual meaning of the four selected lyrics of the song are used to analyze the data got from the song. Based on research findings, some figurative languages were found in Coldplay’s selected songs. Most of the figurative language which is used in the lyrics of Coldplay’s selected songs is “Hyperbole” which has a great exaggeration used to emphasize a point, and used for expressive or comic effect. The meanings which were found from the song are classified into connotative meanings. The lyrics of Coldplay’s selected songs tell us about humanity’s social life which contains love, sadness, happiness, spirit and others. In the lyrics of Coldplay’s selected songs, figurative languages are helpful to understand the song. The existence of figurative language is not to complicate the understanding of lyrics but to simplify and clear the understanding of lyrics. The song is very suitable for English Learners who want to improve their English skills in analyzing lyrics that contain figurative language. From the explanation above can be concluded that in analyzing lyrics besides finding figurative language in lyrics, the meanings of the song that contain figurative languages and messages of the song can be understood.